Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/nmo.12327
|View full text |Cite
|
Sign up to set email alerts
|

The neurochemical changes in the innervation of human colonic mesenteric and submucosal blood vessels in Ulcerative colitis and Crohn's disease

Abstract: There is an increase in SP and TRPv1, and a reduction in SOM immunoreactive nerve fibres in IBD. Changes in the perivascular functional nerve subclasses may underlie the hyperaemia, and ulceration, characteristic of IBD. Furthermore, pain may relate to underlying neural changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 60 publications
2
21
0
1
Order By: Relevance
“…Global sympathectomy can ameliorate and exacerbate colitis, depending on the model used (see summary in 31 ). Presently, we found a decrease in sympathetic nerve density (Figure 3), which is consistent with modestly decreased TH axons in gut submucosal arteries in 2,4,6-Trinitrobenzenesulfonic acid (TNBS) colitis 32 but in contrast to unchanged TH nerves in human submucosal arteries 33 and increased TH nerves in human MAs 34 with IBD. Sensory denervation exacerbates colitis in female oxazolone-induced 35 , TRPV1 -/-Dextran Sulfate Sodium (DSS)induced 36 mouse models and some TNBS-induced rat models 37, 38 but improves colitis in a different TNBS rat model 39 and DSS and TNBS mouse models 40 .…”
Section: Discussionsupporting
confidence: 80%
“…Global sympathectomy can ameliorate and exacerbate colitis, depending on the model used (see summary in 31 ). Presently, we found a decrease in sympathetic nerve density (Figure 3), which is consistent with modestly decreased TH axons in gut submucosal arteries in 2,4,6-Trinitrobenzenesulfonic acid (TNBS) colitis 32 but in contrast to unchanged TH nerves in human submucosal arteries 33 and increased TH nerves in human MAs 34 with IBD. Sensory denervation exacerbates colitis in female oxazolone-induced 35 , TRPV1 -/-Dextran Sulfate Sodium (DSS)induced 36 mouse models and some TNBS-induced rat models 37, 38 but improves colitis in a different TNBS rat model 39 and DSS and TNBS mouse models 40 .…”
Section: Discussionsupporting
confidence: 80%
“…It should be pointed out that in contrast to the stomach and small intestine, knowledge about the distribution of CGRP in the descending colon is rather scanty [ 20 ]. Nevertheless, previous studies have shown some similarities between humans [ 13 , 41 ] and pigs [ 20 , 31 ]. Therefore, it is relatively well known that there is a resemblance between these species with regards to physiological, neuronal and biochemical organization in the ENS [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients with CD have an increased perivascular nerve density around the mesenteric artery, suggesting that neurogenic inflammation may be involved in increased vasodilation and edema observed in chronic inflammatory diseases, such as CD. 209 Meanwhile, changes in blood flow and angiogenesis may result in dysfunction of adipocytes and accumulation of visceral fat mass. Lymphatic vessels mediate lipid absorption and transportation, share an intimate spatial association with adipose tissue, and regulate the traffic of immune cells, 210,211 whereas neuropeptides, such as substance-P (SP), have substantial effects on lymphatic functions, creating lymphatic function and inflammation.…”
Section: Cross Talk Between Mesenteric Tissuesmentioning
confidence: 99%